ZOROASTRIAN (MAGI) CONDITION UNDER THE AUSPICES OF ISLAM AND ITS SPREAD IN INDIA - Efendi; Darni Yusna (Fakultas Agama Islam Universitas Wiralodra, 2022)
The Zoroastrian religion is known as Zoroastrianism. It is an ancient religion that appeared in Asia. It is the official religion of several ancient empires in Asia, the most important of which is Persia or the Sassanid state. Their number ranges between 145 thousand to 2.6 million people, and Zoroastrianism or Magus is one of the oldest religions in the world, as its emergence dates back to approximately 3,500 years. This religion is considered a religion that believes in Two gods' existence: the God of evil and good and light. The question is: Are the Magi from the People of the Book? By 632 AD Yazdegerd III came to power in Persia, but the Arab/Muslim army had already begun conquering Persia. The Muslims defeated them at Nahavand and killed Yazdegerd by a mill at Merv in 652, putting an end to the Sassanid dynasty and thus to the official history of Zoroastrian Iran. While they lost their religion and writing and some Sassanid historical literature, language and culture essentially survived. Political and social pressures led to Iranian Muslims over Zoroastrians between the seventh and thirteenth centuries. With the conquests, the Iranians gradually lost their dominant religion. Zoroastrians moved to India in successive migrations in the Islamic era. The initial migration that followed the conquest has been described as religious persecution through the conquest of Muslims, some persisted in the religion, and some fled Central Asia and India